2011
DOI: 10.1680/bren.900030
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for assessment Eurocodes for bridges

Abstract: The new structural Eurocodes offer increased economy in design over most existing codes of practice. However, the assessment of existing structures is specifically outside the scope of the Eurocodes, so many of the benefits these new codes bring cannot be directly applied when reviewing old structures. This paper investigates the areas where the steel and concrete Eurocodes give increased resistances compared to existing codes and makes recommendations for sections that could be directly applied to the assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The Eurocodes are commonly accepted as having greater economy in design capacities than previous codes of practice (Hendy et al, 2011), being based on more recent design techniques and testing data. Currently there are no assessment codes based on Eurocodes, which means that existing structures are essentially being assessed using superseded techniques and test data, potentially missing out on any benefits which could be brought by applying the latest industry best practice.…”
Section: The Problemmentioning
confidence: 99%
“…The Eurocodes are commonly accepted as having greater economy in design capacities than previous codes of practice (Hendy et al, 2011), being based on more recent design techniques and testing data. Currently there are no assessment codes based on Eurocodes, which means that existing structures are essentially being assessed using superseded techniques and test data, potentially missing out on any benefits which could be brought by applying the latest industry best practice.…”
Section: The Problemmentioning
confidence: 99%
“…Coupon testing of steel from the boxes confirmed that the steel did, however, have adequate ductility to satisfy Eurocode requirements. 'Recommendations for assessment Eurocodes for bridges' (Hendy et al, 2011) gives further details of considerations for using Eurocodes for assessment.…”
Section: Steel Box Girdersmentioning
confidence: 99%
“…In the first of these, the authors investigate how the new structural Eurocodes for steel and concrete might be applied to the assessment of existing structures (Hendy et al, 2011). It is identified that they lend themselves to adaptation and provide a basis for making a rigorous and accurate prediction of the ultimate strength of a structure based on structure-specific loads and material properties.…”
mentioning
confidence: 99%